Exploring Gen Z Sustainable Behavior in the Hospitality Industry - Roberta Minazzi; Daniele Grechi (Administrative Sciences, 2025)
This study investigates Generation Z’s perceptions and behaviors regarding sustainable practices in the hospitality sector, with a particular focus on the gap between intentions and actual behaviors. A significant attitude–behavior gap emerges: while the majority (69%) reports adopting sustainable practices in daily life, only 30% actively reduce air travel. Through exploratory analysis, this study contributes to the existing literature by examining sustainability perceptions as key drivers in hotel selection, offering both theoretical and practical implications for the tourism industry. The data were collected through questionnaires and processed using descriptive and inferential statistics, specifically hypothesis testing tools. The findings indicate that while Gen Z exhibits strong environmental consciousness, economic constraints remain a barrier to sustainable choices. This research suggests that tourism companies need to develop targeted strategies to make sustainable options more accessible, considering both environmental sensitivity and financial limitations of the younger generation. This work addresses a notable gap in the tourism literature regarding travelers’ perceptions of sustainable practices, particularly focusing on Generation Z as an emerging market segment.